Apoptosis Sel-sel Spermatogenik Tikus Putih (Rattus norvegicus) Akibat Pajanan Plumbum (Pb)Serta Perbaikannya Setelah Pemberian Kitosan - Thomson Parluhutan Nadapdap (Universitas Negeri Medan, 2015)
Programmed cell death (apoptosis) of white rat spermatogenic cells can be caused by several factors, including heavy metals such as Cu, Au, Hg, Cd and Pb. The heavy metals found in industrial environments and some public places such as highways and oil pump. This study aims to reduce the negative effects of Pb by using chitosan obtained from shrimp shell processing of the garbage discarded in some shrimp producing areas. This study is divided into six treatment groups K1 = control; K2 = Pb; P1 = Pb+chitosan 0.5%; P2 = Pb = 0.75% chitosan, P3 = Pb+chitosan 1%, P4 = Pb+chitosan 1%. The results showed that administration of Pb causes apoptosis in spermatogenic cells (spermatogonia 78.26%; 84.7% spermatocytes, 77.1% spermatocytes). The addition of 1% chitosan is the best fix apoptotic spermatogenic cells after administration of Pb (Plumbum acetate). Keywords: apoptosis, cells spermatogenic, plumbum, chitosan.